Kernspintomographie des Knochenmarks bei Karzinompatienten mit einer solitären Mehranreieherung im Skelettszintigramm - Smolarz, Kamilla; Jungehülsing, M.; Krug, Barbara; Linden, A.; Göhring, U.-J.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 1990)
Solitary abnormalities in bone scintigrams of cancer patients are a finding causing special diagnostic problems. In a prospective study the value of MRI imaging of the bone marrow was to be ascertained when compared to recognized X-ray studies, as a method of clarifying suspect bone scintigraphy findings. 25 cancer patients presenting with a solitary suspect abnormality in bone scintigrams were examined by X-rays and MRI. In 15 patients, MRI showed that metatases were the probable cause of the hot spot. In 7 patients, radiography, the routinely used method to confirm or exclude the presence of metastases, failed to detect these metastases. In the remaining 10 patients other causes of increased activity in the bone scintigrams could be demonstrated, e.g. fracture, degenerative disease, benign tumour. The results were confirmed by biopsy, operation, autopsy or follow-up. Considering the clinical consequences of the diagnosis of bone metastases, we suggest that a bone marrow MRI of the affected region should be performed to clarify the cause of a solitary hot spot in bone scintigrams of cancer patients, especially if X-ray studies are inconclusive.